Implementation of Character Education for Creating Integrity Schools A Case Study At Public Junior High School 2 Pekalongan in 2015 - Karyono, Karyono; Suyahmo, Suyahmo; Utomo, Cahyo Budi (JESS (Journal of Educational Social Studies), 2019)
The implementation of integrity character has not run optimally yet. Facts show that in various regions, national exams were colored by multiple forms of fraud involving students, teachers, and even school principals. The purpose of this study is to describe and analyze school culture and learning practices as the implementation of character education in Public Junior High School 2 Pekalongan. The research method uses a qualitative approach with data collection techniques through observation, interviews, and document studies. Observation and interviews are used to analyze school culture, while the learning process uses document studies, views, and interviews. The validity of the data in this study uses source triangulation techniques and methods. The results showed the implementation of character education through school culture begins with incorporating character values into the school curriculum, the formation of character building teams, and routine and spontaneous habituation activities, the implementation of character education through the learning process; analyze the character values in Core Competencies (KI), and Basic Competencies (KD), enter character values into the syllabus, Learning Implementation Plan (RPP) and evaluation. Learning subjects in Social Sciences, Islamic Religious Education, Citizenship Education, Indonesian Language, Mathematics, Natural Sciences have integrated character values according to Learning Implementation Plan, while the subjects Sports and English character values have not been implemented according to Learning Implementation Plan.